Radiative sky cooling-assisted thermoelectric cooling system for building applications. (1st January 2020) - Zhao, Dongliang; Yin, Xiaobo; Xu, Jingtao; Tan, Gang; Yang, Ronggui
Abstract: Thermoelectric cooling suffers from low energy conversion efficiency ( i.e., COP) which is a major bottleneck that hurdles its wide application, especially for large-scale systems. The COP of thermoelectric cooling system can be improved by integrating with other technologies. Due to its "free" nature, radiative sky cooling technology can potentially be integrated with thermoelectric cooling to obtain much higher system COP. This study introduces a novel radiative sky cooling-assisted thermoelectric cooling (RSC-TEC) system. The system has four different working modes under different operating conditions. A case study has been conducted for a two-story residential building that has 223 m 2 living zone area located in Los Angeles, USA. Sensitivity analysis is first performed to size the system parameters. It is shown that the RSC-TEC system with a 0.83 m 3 cold storage tank, 32 m 2 radiative cooling surface area, and 101 thermoelectric modules (Laird ZT8-12), could achieve annual cooling COP of 1.87. Further analysis showed that daytime and nighttime cooling of the radiative sky cooling subsystem contribute to 55.0% and 45.0% of annual cold generation (heat dissipation) respectively, which indicates the critical importance of daytime cooling. The RSC-TEC system demonstrates a potential solution for large-scale adoption of the thermoelectric cooling technology. Highlights: A radiative sky cooling assisted thermoelectric cooling (RSC-TEC) system is proposed. Sensitivity analysis is performed to size the system parameters. Annual building energy simulation is conducted with EnergyPlus and MATLAB. Annual cooling COP of 1.87 is achieved in a two-story residential building. The RSC-TEC system demonstrates a potential solution for the wide adoption of thermoelectric cooling technology.